Answer:
No table given, see below
Step-by-step explanation:
I don't see a table, but the first 5 terms are 11, 8, 5, 2, and -1
Answer:
question 13 = D
Step-by-step explanation:
because you do some math, open a calculator and boom, you have that.
Answer:
The correct option is A.
Step-by-step explanation:
Domain:
The expression in the denominator is x^2-2x-3
x² - 2x-3 ≠0
-3 = +1 -4
(x²-2x+1)-4 ≠0
(x²-2x+1)=(x-1)²
(x-1)² - (2)² ≠0
∴a²-b² =(a-b)(a+b)
(x-1-2)(x-1+2) ≠0
(x-3)(x+1) ≠0
x≠3 for all x≠ -1
So there is a hole at x=3 and an asymptote at x= -1, so Option B is wrong
Asymptote:
x-3/x^2-2x-3
We know that denominator is equal to (x-3)(x+1)
x-3/(x-3)(x+1)
x-3 will be cancelled out by x-3
1/x+1
We have asymptote at x=-1 and hole at x=3, therefore the correct option is A....
Its A because 25 is taken out of m=bday money m-$25
Answer: solutions are the same, just written differently, inequality sign is reversed when multiplying by a negative. Yes, both students are correct.Jul 8, 2018
Step-by-step explanation: